An experimental study of the influence of a moving person on airflow characteristics and thermal conditions with diffuse ceiling ventilation. Issue 6 (July 2020) - Zhao, Weixin; Lestinen, Sami; Kilpeläinen, Simo; Kosonen, Risto
The influence of occupants'' movements should be considered when analysing local thermal comfort. This study presents the effect of human movement on airflow characteristics and local thermal conditions with diffuse ceiling ventilation by experimental studies. A simulated person moving was used to study the human movement in an office. In these experiments, three moving speeds were studied: 0.3, 0.6 and 1.0 m/s. The simulated person moved in four cycle patterns: continuous moving and with 5 s, 10 s and 15 s interval breaks between each turn. Three heat gain levels of 40, 60 and 80 W/m 2 were evaluated in the chamber. The results indicate that the human movement decreased vertical temperature gradient compared with the steady-state condition. Instead, the moving intervals would have no effect on the vertical air temperature gradient. The power spectral density was increased by 90% due to the person movement compared with the steady-state condition. The moving person would create different micro-environments close to work stations than close to the moving area.